Análises térmica e energética no pré-aquecimento do revestimento refratário de panelas de aciaria via métodos numéricos e experimentais - Portilho, Tamires Miranda Milagres (2022)
Preheating the refractory lining of industrial equipment usually consumes substantial amounts of energy. This step is usually time consuming and impacts the costs and productivity of several economic sectors. Therefore, cost-effective, and sustainable heating practices should be studied and implemented. Additionally, this step is critical to the refractory and the industry that deploys it because the material faces transformations when heated up to the usual process temperatures, such as the evaporation of water, the elimination of volatile materials, or reactions in the solid state. Based on that, it is necessary to ensure the quality of these materials by applying an appropriate heating curve. This work aims to quantify the energy consumption during the preheating of the refractory lining of a steel ladle. To this end, DSC tests, thermal analysis, and computer simulations were carried out on refractory concrete to evaluate the influence of transformations on the heating step. The simulations for an alumina-based castable, considering the thermal analysis of a cylindrical sample, showed a maximum temperature difference in the first heating of 2 ºC between the experimental value and that obtained by the simulation, proving to be suitable for the quantification of energy consumption during preheating. The simulation, considering the profile obtained in the DSC test, was not satisfactory to represent the energy rate per unit volume of the 5CAC castable. The fuel consumption was 1.8% higher for the case where the energies of the reactions were considered. The developed methodology can bring greater predictability to the preheating schedule of steel ladles, both in terms of fuel consumption and programming the heating curve.